2016
DOI: 10.1111/wre.12225
|View full text |Cite
|
Sign up to set email alerts
|

Weed species composition of conventional soyabean crops in Hungary is determined by environmental, cultural, weed management and site variables

Abstract: The goal of this study was to identify factors determining weed species composition in soyabean crops in Hungary, where its expanding production faces difficult weed problems. The abundance of weed flora was measured in 262 fields across the country, along with 38 background variables. Using a minimal adequate model containing 24 terms with significant net effects, 21.6% of the total variation in weed species data could be explained. Plot location (edge vs core position, the single site variable in our analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 38 publications
14
28
1
Order By: Relevance
“…3). This is in accordance with the findings of other Hungarian (Pinke et al, 2016(Pinke et al, , 2013(Pinke et al, , 2012 and similar European studies (de Mol et al, 2015;Lososov a et al, 2004), where climatic and edaphic factors were more important than land use. Anyway, it should be noted that large gradients can positively influence the importance of environmental factors.…”
Section: Environmental Variablessupporting
confidence: 93%
See 2 more Smart Citations
“…3). This is in accordance with the findings of other Hungarian (Pinke et al, 2016(Pinke et al, , 2013(Pinke et al, , 2012 and similar European studies (de Mol et al, 2015;Lososov a et al, 2004), where climatic and edaphic factors were more important than land use. Anyway, it should be noted that large gradients can positively influence the importance of environmental factors.…”
Section: Environmental Variablessupporting
confidence: 93%
“…Our earlier studies showed that due to their large gradient length, environmental factors were the most important drivers in determining the weed species composition in Hungarian summer arable weed vegetation (Pinke et al, 2012) and also in soybean fields (Pinke et al, 2016). Hungarian oil pumpkin production is generally concentrating in three different regions in the western, south-eastern and northern part of the country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, soil physical and chemical properties, such as texture, Ca, K, Mg, P and humus content, exerted significant effects on the occurrence of certain weed species (Pinke et al ., , ). For example, we found that Cirsium arvense (L.) Scop., a species common in all crop types, preferred soils with high humus and Mg content, but avoided alkaline soils.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent European study soil texture, soil pH and altitude were also among the most important factors determining weed species composition in conventional soybean fields (Pinke et al, 2016). In Europe and even on other continents weed species composition in different crops was most affected by edaphic factors (especially soil pH and soil texture) and altitude (Hanzlik and Gerowitt, 2016 …”
Section: Resultsmentioning
confidence: 99%